A Study of Utilizing of Recycled Concrete Specimens - คำพุฒ ประชุม (Frontiers in Engineering Innovation Research, 2006)
This research is to study the utilizing of recycled concrete specimens in both forms of cylindrical and cubic. There are 2 means of advantage: direct mean (the concrete does not pass the process of crushing) such as covering the soil surface for protect the soil surface. planted the trees. organize the garden and use for roadside in the traffic. indirect mean (the concrete pass the process of crushing), the concrete is reused as coarse aggregate instead of rock in concrete for the parts of building which do not require high compressive strength of concrete. The sieve analysis according with ASTM C 136 is performed to have the same size standard as coarse aggregate in concrete. After testing. the properties of the recycled concrete were found; the average absorption = 4.59%. the specific gravity = 1.97, design the mixed ratio cement: sand: recycled concrete = I : 2: 4 by weight. Then making an examination by casting a cube sizing of 15 x 15 x 15 cu.crn. followed the BS 1881 standard and using water cement ratio = 0.45. 0.50 and 0.55 . The result showed the average bulk unit weight is 2222 . 2242 and 2261 kg/cu.m respectively and the average compressive strength at 28 days = 357. 346 and 33 1 ksc. The compressive strength of normal concrete (mixed with rock) = 389. 380 and 372 ksc respectively. This research showed that recycled concrete could be well utilized in both means (direct and indirect means ).